Gibalna pismenost – temelj zdravja in dobrega počutja - Kukovica, David (Šport (Ljubljana), 2024)
Physical literacy, increasingly recognised as a key element in promoting health and well-being on a global level, combines motivation, confidence, physical competence, knowledge and understanding to enable individuals to value and responsibly participate in physical activity throughout their lives. Although there are different definitions of physical literacy, which can make measurement and interpretation of findings difficult, experts agree that it is important for reducing the risk of chronic diseases and promoting physical, psychological, social and cognitive well-being. This article highlights the complexity of physical literacy, which encompasses physical, psychological, social and cognitive domains, and its importance in promoting healthy lifestyles and improving public health. Research shows a link between high levels of physical literacy and better health indicators, including body mass index, waist circumference, body weight, grip strength and cardiorespiratory fitness. In addition, physical literacy promotes daily physical activity and reduces sedentary behaviour, which is crucial for the prevention of modern health problems. Improving physical literacy and public health requires comprehensive approaches that include the development of physical activity skills from early childhood, the integration of physical activity into education systems and the promotion of policies and programmes to support these goals.
Keywords: dobro počutje; gibalna dejavnost; gibalna pismenost; health; javno zdravje; physical activity; physical literacy; public health; sport; šport; well-being; zdravje